The Blackwell Handbook of Organizational Learning and Knowledge Management - Easterby - Smith Mark; Lyles Marjorie A (Blackwell Publishing, 2005)
The handbook shows perfectly what has been achieved in the field of KM and OL, but also clearly demonstrates the gap in our research and the need to start a dialogue, to fight and unite, to build bridges between old and emerging management disciplines. Foreword, Introduction: Watersheds of Organizational Learning and Knowledge Management, Disciplinary Perspectives, Psychological Perspectives Underlying Theories of Organizational Learning, Social Learning Theory: Learning as Participation in Social Processes, Knowledge Management: The Information Technology Dimension, Organizational Learning and Learning Organizations, Organizations as Learning Portfolios, The Impact of Intercultural Communication on Global Organizational Learning, Absorptive Capacity: Antecedents and Models and Outcomes, Organizational Knowledge and Knowledge Management, Knowledge Management and Competitive Advantage, Dominant Logic and Knowledge Creation and Management Choice, Knowledge Sharing and the Communal Resource, Organizational Forgetting, Knowledge and Networks, Problematizing Organizational Learning and Knowledge, Social Identity and Organizational Learning, Emotionalizing Organizational Learning, Learning from Organizational Experience, Index.